Halide perovskite nanocrystals for multiphoton applications - He, Huajun (2020)
Halide perovskite nanocrystals (NCs) are a unique class of NCs with novel properties distinct from traditional semiconductor NCs. These exceptional properties of defect tolerance, large absorption coefficients, high brightness, and narrow emission linewidths stem from their atypical band structure. Their facile synthesis and broad colour tunability have garnered widespread interests for applications in light emitting devices and lasers. One fledging niche area is the field of multiphoton excited emission where their giant nonlinear optical action cross-sections are highly favorable for imaging applications. This Frontier article examines the state-of-the-art in perovskite NCs for multiphoton applications from the materials science and physics perspectives that include their synthesis and non-linear optical characterization. In particular, opportunities and challenges for these exceptional perovskite NCs as potential fluorescence labels for multiphoton deep tissue microscopy are highlighted.